Surface Decoration of Selenium Nanoparticles by Proteins from the Culinary-Medicinal Shiitake Mushroom, Lentinus edodes (Agaricomycetes), for Enhanced Fibrinolytic Activity - Ali, Sharjahan Mohamed; Raman, Jegadeesh; Lakshmanan, Hariprasath; Ling, Tau Chuan; Phan, Chia Wei; Tan, Yee Shin; Sabaratnam, Vikineswary (Begell House, 2018)
Lentinus edodes (shiitake mushroom) has exhibited fibrinolytic activity. We synthesized and characterized selenium nanoparticles (SeNPs) using protein precipitated from the mushroom. We also investigated the fibrinolytic activity of the SeNPs. The proteins from a crude extract of L. edodes were recovered through the use of aqueous 2-phase separation, and these we used as the capping agent in SeNP biosynthesis. We characterized the SeNPs using UV-visible spectrophotometry, field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX), transmission electron microscopy (TEM), particle size distribution analysis, and Fourier transform infrared spectroscopy (FT-IR). The fibrinolytic capability of the SeNPs was tested through an in vitro fibrin plate assay. The UV-visible spectra showed maximal absorbance at 220 nm. FESEM images showed that the SeNPs were dispersed and did not clump. The TEM images revealed a spherical shape and average size of the SeNPs. The particle size distribution analysis confirmed the mean size of the SeNPs at 64.53 nm. A strong signal for the presence of selenium was observed in the EDX analysis. The FT-IR spectrum revealed the involvement of protein functional groups in the reduction of sel-enite. Overall, the SeNPs capped with protein from shiitake mushroom were effective as an in vitro fibrinolytic agent.